Pengawasan Pemungutan Retribusi Parkir di Tepi Jalan Umum di Kota Sungai Penuh - Dara, Dara Monika; Andora, Hengki; Rosari, Anton (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
In order to realize levies that reach targets, of course there must be good management and supervision from the regional government, whether it is the Transportation Agency as the manager and collector of levies, the DPRD as the legislative function that prepares and establishes regional regulations. The problems that the author raises are; First; How is the supervision carried out by the Sungai Banyak Government in achieving the revenue target from collecting parking fees on the side of public roads? Second; What is the parking levy collection system on the side of the third public road; How to enforce the law against collecting parking fees that do not have an official permit. This research was also carried out using an empirical juridical approach, namely research based on field research as primary data and to complement and support field data, library data was needed as secondary data. Primary data was obtained through interviews with informants from the Transportation Department, Satpol PP, DPRD, Bakeuda, Parking Attendants and the Parking User Community and secondary data was obtained through literature study. All data obtained from field research and literature will be analyzed qualitatively and described descriptively. Based on the research results, it was concluded that the supervision carried out by several related parties was not effective, as can be seen from the failure to achieve the levy target for the parking sector. The levy collection system is not carried out in accordance with the provisions, seen from withdrawals that do not use tickets and deposits of levy proceeds are not carried out every day. Law enforcement against violators is not effective, as can be seen from the large number of illegal parking lots and illegal fees at official and unofficial parking points.